Characterizing the Effects of Heparin Gel Stiffness on Function of Primary Hepatocytes - You, Jungmok (Mary Ann Liebert, Inc., 2013)
In the liver, hepatocytes are exposed to a large array of stimuli that shape hepatic phenotype. This in vivo microenvironment is lost when hepatocytes are cultured in standard cell cultureware, making it challenging to maintain hepatocyte function in vitro. Our article focused on one of the least studied inducers of the hepatic phenotype—the mechanical properties of the underlying substrate. Gel layers comprised of thiolated heparin (Hep-SH) and diacrylated poly(ethylene glycol) (PEG-DA) were formed on glass substrates via a radical mediated thiol–ene coupling reaction. The substrate stiffness varied from 10 to 110 kPa by changing the concentration of the precursor solution. ELISA analysis revealed that after 5 days, hepatocytes cultured on a softer heparin gel were synthesizing five times higher levels of albumin compared to those on a stiffer heparin gel. Immunofluorescent staining for hepatic markers, albumin and E-cadherin, confirmed that softer gels promoted better maintenance of the hepatic phenotype. Our findings point to the importance of substrate mechanical properties on hepatocyte function.